Estimation of Serum leukotriene and some interleukin Levels in Women Infected with Trichomonas vaginalis Parasite - Asraa Dawod Farhan (ASJ - Academic Science Journal, 2025)
This case-control study aimed to estimate serum leukotrines IgG, IgA, IgM, Leukotrienes, Interlukin-10, Interlukin-IB and monocyte chemoattractant protein-1 (MCP) in women infected with Trichomonas vaginalis parasite. In the current study, venous blood samples were collected from (100) women infected with Trichomonas vaginalis parasite who visited the Obstetrics and Gynecology Hospital in Diyala Governorate, and whose ages ranged between (18-50) years during the period from 20/08/2023 to 01/12/2023. Also, venous blood samples were taken from (150) healthy women as a control group. In this study, the levels of serum (IgG, IgA, IgM, Leukotrienes، Interlukin-10، Interlukin-IB and monocyte chemoattractant protein-1 (MCP) were estimated.The results showed that the prevalence rate of Trichomonas vaginalis infection in the studied women was 40%. The levels of IgA, IgM, and IgG were significantly elevated (P≤0.05) in the serum of patients compared to the healthy group. Also, the levels of serum LTB4, IL-10, IL-IB, and MCP were significantly increased (P≤0.05) in the patient group compared to the healthy group. It can be concluded from this study that serum levels of (IgG, IgA, IgM, Leukotrienes Interlukin-10, Interlukin-IB and monocyte chemoattractant protein-1 (MCP) were elevated in women infected with trichomonasiasis.